Developing students’ speaking skill through Project- Based Learning. M.A. Thesis Linguistics: 60 14 01 11 - Phạm, Thị Thu Hà (ĐHNN, 2017)
In an attempt to develop English speaking skill for tenth-grade students at An Lao High School by using Project Based Learning, this research addressed two issues: (1) students’ attitudes toward the use of Project Based Learning in their English lessons; (2) the impacts of using PBL on students’ English speaking.